Estimation of soil loss from the upper Rajang sub-catchments in Sarawak, Malaysia during the developement of the Bakun hydroelectric project - Vu, Ngoc Chau (Universiti Malaysia Sarawak, (UNIMAS), 2005)
Changes in the land use and land cover; especially biomass remoual. timber harvesting and agricultural activities in the Balwn catchment during the development of Bakun Hydro-electric Project (HEP) have resulted in considerable soil loss from the area. The objective of this study is to estimate soil loss from the Upper Rajang SubCatchment during the development of the Bakun HEP by using sediment rating curve. Rating curves were constructed for six scenarios using TSS and water level data collected during a field work and those compiled by the Sarawak Hidro Sdn. Bhd. Suspended sediment yields in the catchment were calculated bQJ3ed on equations created from the rating curve and water level data for 2003 and 2004. Sediment yield is taken to be the sum of suspended sediment yield and bed load, the latter being estimated as 20% of sediment yield. The results for suspended sediment yields for the 'best fit' scenario were 36.87 and 40.20 million tonnes in the year 2003 and 2004 respectively. Taking into consideration the bed load contribution, the annual sediment yields in the catchment were 46.09 and 50.25 million tonnes respectively. The result in this study is not very different when compared with the results of an earlier estimated reported in Bakun HEP EIA (I 995). Estimation of soil loss and sediment yield in the catchment is relevant to the overall assessment of the effects of the project development. Appropriate mitigation measures to minimize the soil erosion and sediment yield on the drainage system, especially the effects to the reservoir in the future, were also highlighted in this dissertation.